Limnological parameters in Skarvsnes lakes during the 48th and 49th Japanese Antarctic Research Expeditions in 2007-2008 -Long-term monitoring study- - Kudou, Sakae; Takabe, Yukiko; Kanda, Hiroshi (National Institute of Polar Research, 2009)
P(論文) departmental bulletin paper